Absence of an association between intercellular adhesion molecule 1, complement receptor 1 and interleukin 1 receptor antagonist gene polymorphisms and severe malaria in a West African population. - Bellamy, R; Kwiatkowski, D; Hill, A (1998)
Many genes have been shown to be involved in host susceptibility to the severe forms of Plasmodium falciparum malaria but it is likely that a large number of malaria-susceptibility genes remain to be determined. We conducted a large case-control study of children with the severe forms of this disease-cerebral malaria and severe malarial anaemia--to attempt to identify these genes. Over 1200 children in The Gambia were typed for polymorphisms of the intercellular adhesion molecule 1 (ICAM-1), complement receptor 1 (CR-1) and interleukin 1 receptor antagonist (IL-IRA) genes. None of the polymorphisms typed was significantly associated with severe disease. These data differed significantly from the results of a previous study (Chi 2 = 8.81; P = 0.003) in which the ICAM-1 gene polymorphism was shown to be significantly associated with cerebral malaria in a case-control study of 547 subjects in Kenya. This suggests that there may be heterogeneity in genetic susceptibility to this condition between these 2 African populations.